The Role of CSR and Environmental Transformational Leadership in Shaping Employees’ Environmental Commitment - Diah Retno Wulandaru; Zaqiah Vivi Putri (Relevance: Journal of Management and Business, 2026)
Despite growing scholarly interest in workplace pro-environmental behavior, limited research has simultaneously examined how Corporate Social Responsibility (CSR) and Environmental Transformational Leadership (ETL) interact to shape employees' environmental commitment and, consequently, Organizational Citizenship Behavior toward the Environment (OCBE). This study aims to investigate the effects of CSR and ETL on environmental commitment and its subsequent influence on OCBE among employees in Indonesian organizations. Data were collected from employees across multiple companies operating in Indonesia with a minimum tenure of six months, and hypotheses were tested using structural equation modeling (SEM). The findings reveal that CSR does not significantly predict environmental commitment, suggesting that CSR initiatives in the Indonesian context remain largely externally oriented rather than internalized by employees. Conversely, ETL demonstrates a significant positive effect on environmental commitment, indicating that leaders who model pro-environmental behavior and articulate compelling sustainability visions are more effective in cultivating employees' internal environmental values. Environmental commitment, in turn, significantly and positively influences OCBE, reflecting that employees with stronger environmental commitment are more inclined to voluntarily engage in pro-environmental behaviors beyond formal role requirements. This study contributes to the green human resource management and leadership literature by demonstrating that internal leadership-driven mechanisms are more influential than external CSR strategies in fostering employee-level environmental behavior. Practically, organizations are advised to prioritize environmentally oriented leadership development alongside value internalization processes to translate sustainability commitments into meaningful employee behavior.